2010
DOI: 10.1088/1742-6596/228/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Short-term forecasting of solar energetic ions on board LISA

Abstract: Abstract. LISA (Laser Interferometer Space Antenna) and LISA Pathfinder (LISA-PF) freefalling test-masses are charged by galactic and solar energetic particles. This process generates spurious forces on the test masses which appear as noise in the experiments. It was shown that relativistic solar electron detection can be used for up-to-one-hour forecasting of incoming energetic ions at 1 AU . Warning of incoming solar energetic particle events could allow us to optimize the test-mass discharging. The current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The charging process of the free-floating proof-masses induces spurious forces that might mimic genuine gravitational wave signals in the interferometer bandwidths as it was shown in Ref. 7.…”
Section: Introductionmentioning
confidence: 77%
“…The charging process of the free-floating proof-masses induces spurious forces that might mimic genuine gravitational wave signals in the interferometer bandwidths as it was shown in Ref. 7.…”
Section: Introductionmentioning
confidence: 77%
“…Neither electron nor heavy-ion monitoring will be carried out on LISA-PF. The possibility of modifying the LISA-PF radiation monitors for LISA in order to include solar electron detection for SEP event forecasting was presented in [15].…”
Section: Radiation Detector On Board Lisa-pfmentioning
confidence: 99%
“…Solar and galactic particles with energies greater than 100 MeV/n penetrate the spacecraft charging the test masses [12][13][14]. This process constitutes one of the most important sources of noise for the experiment in the low-frequency range (see for example [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Ions with energies larger than 100 MeV(/n) penetrate the spacecraft and, therefore, particle detector observations will help to estimate the proof mass charging [20,21]. In particular, LISA simulations indicate that solar events with fluences larger than 10 7 protons/cm 2 overcome the whole mission noise budget in the low frequency range in a few tens of minutes ( [22] and references therein).…”
Section: Solar Physics Using Radiation Monitorsmentioning
confidence: 99%
“…Each event lasts a few days. It was evaluated if it was worthwhile to modify the LISA-PF radiation monitors to add SEP forecasting capabilities to LISA [21]. For the ASTROD I mission the test mass charging studies were reported in [23][24] for both galactic cosmic-ray and solar energetic particles.…”
Section: Solar Physics Using Radiation Monitorsmentioning
confidence: 99%